Wearable Sensors: Micropatterned Elastic Gold‐Nanowire/Polyacrylamide Composite Hydrogels for Wearable Pressure Sensors (Adv. Mater. Technol. 7/2018). Issue 7 (12th July 2018) - Yin, Ming‐jie; Zhang, Yangxi; Yin, Zhigang; Zheng, Qingdong; Zhang, A. Ping
Abstract : Elastic hydrogels have recently attracted remarkable attention because of their unique mechanical and stimulus‐responsive properties. In article1800051, A. Ping Zhang and co‐workers present a micropatterned elastic gold‐nanowire/polyacrylamide composite hydrogel for wearable sensor applications. The hydrogel can be directly printed on electrodes to fabricate low‐cost high‐performance pressure sensors and has a wide variety of promising applications ranging from wearable healthcare devices to soft robots.